articleDecline in empathy among healthcareworkers; where have all the flowers gone? - J. C. Charles; B. Sivayokan; T. Kumanan (Sri Lanka College of Internal Medicine, 2024)
Studies from around the world are reporting a decline in the empathy of healthcare workers (HCWs) in recent years. This review article explores the implications of this decline of empathy on patient care and provider well-being, and possible ways to promote empathy among HCWs. Empathy plays a crucial role in fostering therapeutic alliances and enhancing patient outcomes. However, practising clinical empathy poses significant challenges, including emotional exhaustion and burnout, time constraints, professional boundaries, and cultural differences. These challenges contribute to a substantial decline in empathy among HCWs, which is further exacerbated by high-stress environments, heavy workload, and drawbacks in the healthcare system. Junior doctors and medical students are particularly vulnerable to a decline in empathy due to the demands posed by medical education and demanding training periods. Structured programmes promoting self-care practices, fostering supportive work environments, and integrating empathy-focused training into education and practice can be used to teach clinical empathy. However, a conducive atmosphere and a culture of empathy in the clinical setting are also crucial. Furthermore, sustained effort and institutional support are essential to sustain the skills thus taught. Such endeavours would contribute to cultivating compassionate healthcare professionals who prioritise patient-centred care and well-being.